2013
DOI: 10.1155/2013/821813
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide, a Novel NF-κB Inhibitor, Induces Vascular Smooth Muscle Cell Apoptosis via a Ceramide-p47phox-ROS Signaling Cascade

Abstract: Atherosclerosis is linked with the development of many cardiovascular complications. Abnormal proliferation of vascular smooth muscle cells (VSMCs) plays a crucial role in the development of atherosclerosis. Accordingly, the apoptosis of VSMCs, which occurs in the progression of vascular proliferation, may provide a beneficial strategy for managing cardiovascular diseases. Andrographolide, a novel nuclear factor-κB inhibitor, is the most active and critical constituent isolated from the leaves of Andrographis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Apoptosis, the planned cell death, plays key roles in several physiologic processes in cell development (Chen et al, 2013). Failure in apoptosis leads to tumor growth and development as well as resistance to most oncologic therapies (Lowe et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, the planned cell death, plays key roles in several physiologic processes in cell development (Chen et al, 2013). Failure in apoptosis leads to tumor growth and development as well as resistance to most oncologic therapies (Lowe et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, andrographolide, an NF- κ B inhibitor derived from the leaves of Andrographis paniculata , induces apoptosis through generation of ROS. 34 , 35 Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) is an in-tracellular ROS producer. NOX is a complex composed of membrane-bound (p22phox and NOX 1-4) and cytoplasmic (Rac, p47phox, and p67phox) subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduction of the inactive proenzyme form of caspase-3 and cleavage of PARP were also observed in the present study, indicating that it was a caspase-dependent apoptosis. A recent study also revealed that AP 1 induced vascular smooth muscle cell apoptosis via ceramide-p47phox-ROS and caspase-3 signaling cascade [46]. Notably, the intensities of the cleaved active forms of caspase-3 bands (17/19-kD) were very weak (data not shown).…”
mentioning
confidence: 82%